Emerging Issues from Conducting Researches in Tanzania: Reflections from selected cases - Anasel, Mackfallen G.; Swai, Idda L.; Lameck, Wilfred U.; Igulu, George (Journal of Policy and Leadership, 2019)
Different authors in Tanzania have reported on the challenges they encountered from the legal and policy framework in soliciting for a permit and engaging study’s participants for data collection. Bearing those observations, this study draws experiences from the selected cases of four PhD researches conducted in Tanzania between 2011 and 2016. Our researches show that the processes of acquiring permission for field work and data collection varies. The permission to conduct study in some local authorities was granted by executive directors, others, by district administrative secretaries, council chairpersons as well as head of departments. The researchers’ experience in data collection process is completely different when it comes to the actual process of data collection. The experiences provided by the researchers in this study are important towards helping other researchers to understand local-context legal and policy framework specific issues when designing their study.